Static infographics effects on the receptive knowledge of idiomatic expressions - Alrajhi, Assim S. (Universitas Pendidikan Indonesia, 2020)
Idiomatic expressions are essential components of EFL learners’ linguistic repertoire. Nevertheless, learning such inherently perplexing language constructs poses a challenge to learners. Therefore, the present study was motivated by examining a modern tool (infographics) that is relatively under-researched in EFL settings and potentially conducive to fruitful vocabulary learning. Grounded in dual coding (DCT) and cognitive load (CLT) theories, this study aims to examine the effectiveness of visualizing English idioms via static infographics. Data were collected using three instruments (a pre-/post-test, an attitude questionnaire, and semi-structured interviews) in a mixed-method design. The participants consisted of 78 Arabic speaking students at a Saudi university. Divided equally into two groups, these participants were instructed to learn 60 idioms in five computer-mediated sessions. Students in the control group studied the target idioms via online texts, whereas those in the experimental group studied them via online static infographics. The findings show that despite the significant increase in the post-test scores of both groups, the treatment group outperformed the control group as indicated by the statistically significant difference in scores. Consequently, the findings signify a high potential of static infographics to foster receptive knowledge of idioms. Moreover, the participants show positive attitudes toward the utility of static infographics on learning idioms. Meanwhile, the qualitative findings reveal a number of compelling factors induced by productive constituents and adequate content of the infographics. Those factors are conducive to effective learning and retention, triggering motivation and interests, promoting autonomous and efficient learning, and attracting learners’ attention.